Effects of the coronary artery disease associated LPA and 9p21 loci on risk of aortic valve stenosis. (1st February 2019) - Trenkwalder, Teresa; Nelson, Christopher P.; Musameh, Muntaser D.; Mordi, Ify R.; Kessler, Thorsten; Pellegrini, Costanza; Debiec, Radoslaw; Rheude, Tobias; Lazovic, Viktor; Zeng, Lingyao; Martinsson, Andreas; Gustav Smith, J.; et al.
Abstract: Background: Aortic valve stenosis (AVS) and coronary artery disease (CAD) have a significant genetic contribution and commonly co-exist. To compare and contrast genetic determinants of the two diseases, we investigated associations of the LPA and 9p21 loci, i.e. the two strongest CAD risk loci, with risk of AVS. Methods: We genotyped the CAD-associated variants at the LPA (rs10455872) and 9p21 loci (rs1333049) in the GeneCAST (Genetics of Calcific Aortic STenosis) Consortium and conducted a meta-analysis for their association with AVS. Cases and controls were stratified by CAD status. External validation of findings was undertaken in five cohorts including 7880 cases and 851, 152 controls. Results: In the meta-analysis including 4651 cases and 8231 controls the CAD-associated allele at the LPA locus was associated with increased risk of AVS (OR 1.37; 95%CI 1.24–1.52, p = 6.9 × 10 −10 ) with a larger effect size in those without CAD (OR 1.53; 95%CI 1.31–1.79) compared to those with CAD (OR 1.27; 95%CI 1.12–1.45). The CAD-associated allele at 9p21 was associated with a trend towards lower risk of AVS (OR 0.93; 95%CI 0.88–0.99, p = 0.014). External validation confirmed the association of the LPA risk allele with risk of AVS (OR 1.37; 95%CI 1.27–1.47), again with a higher effect size in those without CAD. The small protective effect of the 9p21 CAD risk allele could not be replicated (OR 0.98; 95%CI 0.95–1.02). Conclusions: Our study confirms the association of the LPA locus with risk of AVS, with a higher effect in those without concomitant CAD. Overall, 9p21 was not associated with AVS. Highlights: The Lipoprotein (a) risk variant, LPA shows a robust association with risk of AVS, independent of CAD. The effect size of the LPA risk allele is higher in patients without concomitant CAD. High Lp(a) levels are associated with younger age of need for TAVR, especially in those without CAD. The strongest CAD risk allele at 9p21 is not associated with risk of AVS.